Polymorphism on chromosome 20p13 near the IDH3B gene is associated with uterine prolapse. (September 2020) - Bizjak, Tina; Gorenjak, Mario; Potočnik, Uroš; But, Igor
Abstract: Objectives: Previous studies have found evidence for a genetic basis for pelvic organ prolapse (POP), but no genetic studies have differentiated between types of POP. This study investigated whether genetic variants in six previously suggested candidate loci for POP modify the risk of uterine prolapse (UP). Study design: One hundred patients, aged 30–55 years, who had undergone surgery due to total UP and 105 healthy controls were included in this study. After extracting the genomic DNA from peripheral blood, six single nucleotide polymorphisms (SNPs) previously identified for POP were genotyped, and association analysis was performed for contributing risk factors. RNA expression was determined from sacrouterine ligaments of patients and controls using quantitative reverse transcription polymerase chain reaction. Results: The dominant genotype model for the T allele for SNP rs6051098 at the chromosome 20p13 locus was significant, and this remained significant with the risk factor regression model ( p= 0.046; odds ratio 1.93, 95 % confidence interval 1.01–3.66). The isocitrate dehydrogenase 3 beta ( IDH3B ) gene was the only potential candidate gene in the 20p13 locus that was significantly upregulated in sacrouterine biopsies in women with UP compared with controls ( p  = 0.034). Conclusion: To the best of the authors' knowledge, this is the first study to show that genetic risk factors contribute to UP, and suggested rs6051098 as the best candidate risk factor associated with UP. According to expression data in sacrouterine tissue, this study suggests that the IDH3B gene plays a role in the pathogenesis of UP.